High-temperature-resistant fireproof cable and preparation method thereof

By designing a multi-layer structure in the cable, including silicone-nanoalumina sol insulating layer, composite flame retardant material fire-retardant layer and polyurethane elastomeric outer sheath, the problem of poor performance of existing cables in high temperature and fire environments is solved, and the excellent high temperature and fire-resistance of the cable is achieved.

CN119581123AInactive Publication Date: 2025-03-07HANGZHOU XINGFA TRANSMISSION EQUIP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410998626.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing cables have poor performance in high temperature and fire environments, making it difficult to meet the dual requirements of high temperature resistance and fire resistance at the same time, and the preparation process is complex and costly.

Method used

The cable design is adopted including conductors, insulating layers, fire-retardant layers and outer sheath. The insulating layer is an insulating impregnated paint coated with quartz fiber wrapping layer. The fire-retardant layer is composed of polystyrene, low-density polyethylene, hydrotalcite, composite flame retardant materials, compatibility agents and crosslinking agents. The outer sheath is a polyurethane elastomer.

Benefits of technology

The electrical performance and mechanical stability of the cable in high-temperature environments are achieved, and the flame retardant performance of the cable is significantly improved through the multi-layer protection mechanism, which is suitable for high-temperature and high-risk industrial environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004960953660000071
    Figure BDA0004960953660000071
  • Figure BDA0004960953660000081
    Figure BDA0004960953660000081
  • Figure BDA0004960953660000082
    Figure BDA0004960953660000082
Patent Text Reader

Abstract

The invention relates to the technical field of cables, and particularly discloses a high-temperature-resistant fireproof cable and a preparation method thereof. The high-temperature-resistant fireproof cable comprises a conductor, an insulating layer, a fireproof layer and an outer protective layer, the insulating layer is a quartz fiber wrapping layer coated with organic silicon-nano aluminum oxide sol insulating impregnating varnish; the fireproof layer is prepared from the following raw materials: polystyrene, low-density polyethylene, hydrotalcite, a composite flame-retardant material, a compatilizer and a cross-linking agent. A preparation method of a high-temperature-resistant fireproof cable comprises the following steps: S1, wrapping a conductor with quartz fibers, coating the quartz fibers with organic silicon-nano aluminum oxide sol insulating impregnating varnish, and drying to obtain an insulating layer; s2, stirring and mixing the raw materials of the fireproof layer, and extruding and granulating; and S3, sequentially coating the outer surface of the insulating layer with a fireproof layer and an outer protective layer to obtain the high-temperature-resistant fireproof cable. The high-temperature-resistant fireproof cable prepared by the invention has excellent high-temperature-resistant performance and flame-retardant and fireproof performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of cable technology, and in particular to a high temperature resistant and fireproof cable and a preparation method thereof. Background Art

[0002] At present, with the continuous development of the power system, the performance requirements for cables are getting higher and higher. Especially in high temperature and fire environments, traditional cables are easily damaged, resulting in power transmission interruptions and even greater safety hazards. There are some high temperature resistant cables and fireproof cables on the market, but they can usually only meet a single performance requirement, either poor high temperature resistance or unsatisfactory fireproof effect. At the same time, the preparation process of these cables is complicated and the cost is high. Therefore, it is particularly important to develop a high temperature resistant and fireproof cable. Summary of the invention

[0003] In order to solve at least one of the above technical problems, a cable with excellent high temperature resistance and fire resistance is developed. The present application provides a high temperature resistant and fireproof cable and a preparation method thereof.

[0004] On the one hand, the present application provides a high temperature resistant fireproof cable, comprising a conductor, an insulating layer, a fireproof layer and an outer sheath; the insulating layer is a quartz fiber sheath coated with an organic silicon-nano alumina sol insulating impregnation varnish; The fireproof layer comprises the following raw materials in parts by weight: 50-60 parts of polystyrene, 30-40 parts of low-density polyethylene, 14-20 parts of hydrotalcite, 7-10 parts of composite flame retardant material, 1.3-3.2 parts of compatibilizer, and 0.3-3 parts of crosslinking agent.

[0005] By adopting the above-mentioned technical scheme, the high temperature resistant and fireproof cable in this application combines the performance of the insulation layer, fireproof layer and outer sheath materials, which not only ensures the electrical performance and mechanical stability of the cable in a high temperature environment, but also effectively improves the flame retardant performance of the cable through a multi-layer protection mechanism. It is suitable for use in high temperature and high-risk industrial environments.

[0006] Optionally, the method for preparing the composite flame retardant material comprises the following steps: A1. Add the hollow glass microspheres to a 2 wt% NaOH solution, mix and stir, filter, wash, dry and then crush to obtain a pretreated hollow glass microsphere powder; A2, adding the pretreated hollow glass microsphere powder obtained in step A1 to ethanol and mixing, and then adding KH550 and mixing to obtain a mixed solution; A3, adding ammonium polyphosphate to ethanol and mixing and stirring to obtain an ammonium polyphosphate solution with a mass concentration of 18-22%; mixing and stirring the ammonium polyphosphate solution with the mixed solution obtained in step A2, filtering, washing, drying and then crushing to obtain ammonium polyphosphate-hollow glass microsphere powder; A4, adding sodium alginate to distilled water and mixing, then adding the ammonium polyphosphate-hollow glass microsphere powder obtained in step A3 and mixing, and freeze-drying to obtain the composite flame retardant material.

[0007] By adopting the above technical scheme, ammonium polyphosphate was grafted on the surface of hollow glass microspheres through silane coupling agent (KH550) and then added to sodium alginate, and a composite flame retardant material was prepared by freeze drying. The ammonium polyphosphate in the prepared composite flame retardant material will be decomposed into polyphosphoric acid and polyphosphoric acid after preheating. Polyphosphoric acid is a strong acid that can dehydrate and carbonize the surface of the material and expand. The carbonized layer attached to the surface of the material can prevent the heat in the environment from entering the matrix material, thereby achieving the purpose of flame retardancy. Secondly, ammonium polyphosphate will produce nitrogen, ammonia, water vapor and other gases during the combustion process. A part of ammonia and oxygen react to generate nitrogen oxides, which not only consumes the oxygen content in the combustion environment, but also takes away a part of the heat, reduces the temperature inside the combustion surface, and can achieve a good flame retardant effect.

[0008] Optionally, in step A2, the weight-to-volume ratio of the pretreated hollow glass microsphere powder, ethanol and KH550 is (5-7) g: 100 mL: (5-7) mL.

[0009] Optionally, in step A3, the volume ratio of the ammonium polyphosphate solution to the mixed solution is (1-2):1.

[0010] Optionally, in step A3, the weight ratio of the sodium alginate to ammonium phosphate-hollow glass microsphere powder is 1:(1-3).

[0011] Optionally, the weight ratio of the hydrotalcite to the composite flame retardant material is 1.8-2.4:1.

[0012] Optionally, the sum of the weights of the hydrotalcite and the composite flame retardant material is 20.4-24.2% of the total weight of the raw materials of the fireproof layer.

[0013] By adopting the above technical scheme, the present application limits the weight ratio of hydrotalcite and the composite flame retardant material in the composite flame retardant material and the proportion of the sum of the weights of the two in the raw materials of the fireproof layer, which can optimize the flame retardant efficiency of the flame retardant layer, enhance the flame retardant properties, and control the density and cost of the material while ensuring the fireproof properties.

[0014] Optionally, the preparation method of the organosilicon-nano alumina sol insulating impregnating varnish is: stirring and mixing organosilicon resin and 30% nano alumina sol at a volume ratio of 1:2.5-3.5 for 2-3 hours to obtain the organosilicon-nano alumina sol insulating impregnating varnish.

[0015] By adopting the above technical scheme, the organosilicon-nano alumina sol insulating impregnation varnish combines the high temperature resistance of organosilicon and the excellent mechanical properties of nano alumina, and then combines it with quartz fiber with good mechanical strength and heat resistance, thereby improving the cable's resistance to thermal shock and high temperature aging.

[0016] Optionally, the outer protective layer is polyurethane elastomer.

[0017] By adopting the above technical solutions, polyurethane elastomer has high abrasion resistance, tear strength and impact resistance, which can effectively protect cables from physical damage. Polyurethane materials can resist a variety of chemicals, oils and solvents, and have good weather resistance.

[0018] In a second aspect, the present application provides a method for preparing the above-mentioned high temperature resistant and fireproof cable, comprising the following steps: S1, wrapping the conductor with quartz fiber, then coating the quartz fiber with organic silicon-nano alumina sol insulating impregnation varnish, and drying to obtain an insulating layer; S2, stirring and mixing the raw materials of the fireproof layer, and extruding and granulating; S3. The fireproof layer and the outer protective layer are sequentially coated on the outer surface of the insulation layer to obtain a high temperature resistant and fireproof cable.

[0019] By adopting the above technical scheme, the cable prepared in the present application has excellent high temperature resistance and fire retardant properties, the preparation method is simple, the production efficiency is improved, and it is conducive to large-scale promotion and application.

[0020] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The high temperature resistant and fireproof cable in this application combines the performance of the insulation layer, fireproof layer and outer sheath materials, which not only ensures the electrical performance and mechanical stability of the cable in a high temperature environment, but also effectively improves the flame retardant performance of the cable through a multi-layer protection mechanism. It is suitable for use in high temperature and high-risk industrial environments.

[0021] 2. The cable prepared in this application has excellent high temperature resistance and fire retardant properties, the preparation method is simple, the production efficiency is improved, and it is conducive to large-scale promotion and application. DETAILED DESCRIPTION

[0022] The present application is further described in detail below with reference to the embodiments. Specific embodiments

[0023] Preparation Example 1-3 Preparation Example 1 This preparation example provides a method for preparing an organic silicon-nano alumina sol insulating impregnating varnish, which comprises stirring and mixing an organic silicon resin and a 30% nano alumina sol at a volume ratio of 1:3 for 2.5 hours to obtain the organic silicon-nano alumina sol insulating impregnating varnish.

[0024] Preparation Example 2-4 Preparation Example 2 This preparation example provides a method for preparing an organic silicon-nano alumina sol insulating impregnating varnish: a method for preparing a composite flame retardant material, comprising the following steps: A1. Add the hollow glass microspheres to a 2 wt% NaOH solution, mix and stir, filter, wash, dry and then crush to obtain a pretreated hollow glass microsphere powder; A2, adding the pretreated hollow glass microsphere powder obtained in step A1 to ethanol and mixing, and then adding KH550 and mixing to obtain a mixed solution; A3, adding ammonium polyphosphate to ethanol and mixing and stirring to obtain an ammonium polyphosphate solution with a mass concentration of 20%; mixing and stirring the ammonium polyphosphate solution with the mixed solution obtained in step A2, filtering, washing, drying and then crushing to obtain ammonium polyphosphate-hollow glass microsphere powder; A4, adding sodium alginate to distilled water and mixing, then adding the ammonium polyphosphate-hollow glass microsphere powder obtained in step A3 and mixing, and freeze-drying to obtain the composite flame retardant material.

[0025] In the step A2, the weight volume ratio of the pretreated hollow glass microsphere powder, ethanol and KH550 is 5g:100mL:5mL.

[0026] In step A3, the volume ratio of the ammonium polyphosphate solution to the mixed solution is 1:1.

[0027] The weight ratio of the sodium alginate to the ammonium phosphate-hollow glass microsphere powder is 1:1.

[0028] Preparation Example 3 This preparation example provides a method for preparing an organic silicon-nano alumina sol insulating impregnating varnish: a method for preparing a composite flame retardant material, comprising the following steps: A1. Add the hollow glass microspheres to a 2 wt% NaOH solution, mix and stir, filter, wash, dry and then crush to obtain a pretreated hollow glass microsphere powder; A2, adding the pretreated hollow glass microsphere powder obtained in step A1 to ethanol and mixing, and then adding KH550 and mixing to obtain a mixed solution; A3, adding ammonium polyphosphate to ethanol and mixing and stirring to obtain an ammonium polyphosphate solution with a mass concentration of 20%; mixing and stirring the ammonium polyphosphate solution with the mixed solution obtained in step A2, filtering, washing, drying and then crushing to obtain ammonium polyphosphate-hollow glass microsphere powder; A4, adding sodium alginate to distilled water and mixing, then adding the ammonium polyphosphate-hollow glass microsphere powder obtained in step A3 and mixing, and freeze-drying to obtain the composite flame retardant material.

[0029] In the step A2, the weight volume ratio of the pretreated hollow glass microsphere powder, ethanol and KH550 is 6 g: 100 mL: 6 mL.

[0030] In step A3, the volume ratio of the ammonium polyphosphate solution to the mixed solution is 1.5:1.

[0031] The weight ratio of the sodium alginate to the ammonium phosphate-hollow glass microsphere powder is 1:2.

[0032] Preparation Example 4 This preparation example provides a method for preparing an organic silicon-nano alumina sol insulating impregnating varnish: a method for preparing a composite flame retardant material, comprising the following steps: A1. Add the hollow glass microspheres to a 2 wt% NaOH solution, mix and stir, filter, wash, dry and then crush to obtain a pretreated hollow glass microsphere powder; A2, adding the pretreated hollow glass microsphere powder obtained in step A1 to ethanol and mixing, and then adding KH550 and mixing to obtain a mixed solution; A3, adding ammonium polyphosphate to ethanol and mixing and stirring to obtain an ammonium polyphosphate solution with a mass concentration of 20%; mixing and stirring the ammonium polyphosphate solution with the mixed solution obtained in step A2, filtering, washing, drying and then crushing to obtain ammonium polyphosphate-hollow glass microsphere powder; A4, adding sodium alginate to distilled water and mixing, then adding the ammonium polyphosphate-hollow glass microsphere powder obtained in step A3 and mixing, and freeze-drying to obtain the composite flame retardant material.

[0033] In the step A2, the weight volume ratio of the pretreated hollow glass microsphere powder, ethanol and KH550 is 7 g: 100 mL: 7 mL.

[0034] In step A3, the volume ratio of the ammonium polyphosphate solution to the mixed solution is 2:1.

[0035] The weight ratio of the sodium alginate to the ammonium phosphate-hollow glass microsphere powder is 1:3.

[0036] Example 1 This embodiment provides a high temperature resistant fireproof cable, comprising a conductor, an insulating layer, a fireproof layer and an outer sheath; The insulating layer is a quartz fiber wrapping layer coated with organic silicon-nano alumina sol insulating impregnation varnish; The fireproof layer comprises the following raw materials in parts by weight: 50 parts of polystyrene, 30 parts of low-density polyethylene, 16 parts of hydrotalcite, 8 parts of composite flame retardant material, 1.3 parts of compatibilizer, and 0.3 parts of cross-linking agent; The outer protective layer is polyurethane elastomer.

[0037] In this embodiment, the organic silicon-nano alumina sol insulating impregnation varnish is prepared by Preparation Example 1; the composite flame retardant material is prepared by Preparation Example 2; the compatibilizer is maleic anhydride grafted polyolefin; and the crosslinking agent is diisopropylbenzene peroxide.

[0038] The preparation method of the high temperature resistant fireproof cable in this preparation example comprises the following steps: S1. Preparation of insulating layer: wrapping the conductor with quartz fiber, coating the quartz fiber with organic silicon-nano alumina sol insulating impregnation varnish, and drying to obtain the insulating layer; S2, stirring and mixing the raw materials of the fireproof layer, and extruding and granulating; S3. Cabling: The fireproof layer and the outer sheath are sequentially coated on the outer surface of the insulation layer to obtain a high temperature resistant and fireproof cable.

[0039] Embodiment 2-4 Example 2 The difference between this embodiment and embodiment 1 is that when preparing the high temperature resistant fireproof cable, the total weight of the hydrotalcite and the composite flame retardant material is 24 parts, and the weight ratio of the hydrotalcite and the composite flame retardant material is 1.8:1.

[0040] Example 3 The difference between this embodiment and embodiment 1 is that when preparing the high temperature resistant fireproof cable, the total weight of the hydrotalcite and the composite flame retardant material is 20 parts, and the weight ratio of the hydrotalcite and the composite flame retardant material is 2.2:1.

[0041] Example 4 The difference between this embodiment and embodiment 1 is that when preparing the high temperature resistant fireproof cable, the total weight of the hydrotalcite and the composite flame retardant material is 20 parts, and the weight ratio of the hydrotalcite and the composite flame retardant material is 2.4:1.

[0042] Comparative Examples 1-3 Comparative Example 1 The difference between this comparative example and Example 1 is that no composite flame retardant material is added when preparing the high temperature resistant and fireproof cable.

[0043] Comparative Example 2 The difference between this comparative example and Example 1 is that no hydrotalcite is added when preparing the high temperature resistant and fireproof cable.

[0044] Comparative Example 3 The difference between this comparative example and Example 1 is that when preparing the high temperature resistant and fireproof cable, no hydrotalcite and composite flame retardant material are added.

[0045] Experimental testing: Flame retardant test: oxygen index test reference standard GB / T 2406.2-2009; High temperature resistance test: Refer to standard GB / T 2951.11-2008 to test the tensile strength after high temperature aging.

[0046] The experimental test results of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.

[0047] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-3 Example Limiting oxygen index / % Tensile strength after aging / MPa Example 1 35 56 Example 2 34 54 Example 3 32 53 Example 4 31 50 Comparative Example 1 22 45 Comparative Example 2 26 46 Comparative Example 3 17 39 Result analysis: The difference between Examples 2-4 and Example 1 is that when preparing a high-temperature fireproof cable, the total weight of hydrotalcite and the composite flame retardant material is 24 parts, and the weight ratio of hydrotalcite and the composite flame retardant material is different. Combined with the experimental test results in Table 1, it can be seen that when the weight ratio of hydrotalcite and the composite flame retardant material is 2:1, the high-temperature resistance and flame retardant properties of the prepared high-temperature fireproof cable. The difference between Comparative Example 1 and Example 1 is that when preparing a high-temperature fireproof cable, no composite flame retardant material is added. The difference between Comparative Example 2 and Example 1 is that when preparing a high-temperature fireproof cable, no hydrotalcite is added. The difference between Comparative Example 3 and Example 1 is that when preparing a high-temperature fireproof cable, no hydrotalcite and composite flame retardant material are added. Combined with the experimental test results in Table 1, it can be seen that when preparing a high-temperature fireproof cable, the compound use of hydrotalcite and composite flame retardant materials can better improve the comprehensive performance of the prepared high-temperature fireproof cable.

[0048] Embodiment 5-6 The difference between Example 5-6 and Example 1 is that the weight percentages of some components are changed when preparing the high temperature resistant and fireproof cable. See Table 2 for the difference.

[0049] 50 parts of polystyrene, 30 parts of low-density polyethylene, 16 parts of hydrotalcite, 8 parts of composite flame retardant material, 1.3 parts of compatibilizer, and 0.3 parts of cross-linking agent; Table 2 - Differences between Examples 5-6 and Example 1 Ingredients (parts by weight) Example 3 Example 5 Example 6 Polystyrene 50 55 60 Low density polyethylene 30 35 40 Hydrotalcite 16 16 16 Composite flame retardant materials 8 8 8 Compatibilizer 1.3 2 3.2 Crosslinking agent 0.3 1.8 3 The experimental test results of Examples 5-6 are shown in Table 3.

[0050] Table 3 - Experimental test results of Examples 5-6 Result analysis: The difference between Example 5-6 and Example 1 is that when preparing high-temperature resistant and fireproof cables, the weight proportions of some components are different. Combined with the experimental test results in Table 1, it can be seen that when preparing high-temperature resistant and fireproof cables, the high-temperature resistant and fireproof cables prepared in Example 5 have better comprehensive performance.

[0051] Embodiment 7-9 The difference between Example 7-9 and Example 5 is that when preparing high temperature resistant and fireproof cables, based on the premise that the weight ratio of hydrotalcite and the composite flame retardant material is 2:1, the proportion of the total weight of hydrotalcite and the composite flame retardant material in the flame retardant antistatic polyurethane elastic is changed, and the optimal weight proportion is selected.

[0052] In Example 5, the total weight of the hydrotalcite and halloysite nanotube-ammonium polyphosphate is 24 parts, and the total weight of the high temperature resistant and fireproof cable is 117.8 parts.

[0053] Therefore, it is not difficult to conclude that in Example 5, the sum of the weights of hydrotalcite (called variable 1) and the composite flame retardant material (called variable 2) accounts for 20.4% of the total weight of the raw materials of the high temperature resistant and fireproof cable (called the matrix).

[0054] The differences between Examples 7-9 and Example 5 are shown in Table 4.

[0055] Proportion = (variable 1 + variable 2) / total weight of matrix * 100%.

[0056] Table 4 - Differences between Examples 7-9 and Example 5 The experimental test results of Examples 7-9 are shown in Table 5.

[0057] Table 5 - Experimental test results of Examples 7-9 Result analysis: The difference between Example 7-9 and Example 5 is that when preparing a high temperature resistant fireproof cable, when the proportion of hydrotalcite (called variable 1) and the composite flame retardant material (called variable 2) in the high temperature resistant fireproof cable (called the matrix) is between (20.4-24.2)%, the comprehensive performance of the prepared high temperature resistant fireproof cable is better. When the proportion of hydrotalcite (called variable 1) and the composite flame retardant material (called variable 2) in the high temperature resistant fireproof cable (called the matrix) is 22.4%, the comprehensive performance of the prepared high temperature resistant fireproof cable is better.

[0058] Embodiment 10-11 Example 10 The difference between this embodiment and embodiment 8 is that, when preparing the high temperature resistant and fireproof cable, the composite flame retardant material in this embodiment is prepared by Preparation Example 3.

[0059] Embodiment 11 The difference between this embodiment and embodiment 8 is that, when preparing the high temperature resistant and fireproof cable, the composite flame retardant material in this embodiment is prepared by Preparation Example 4.

[0060] The experimental test results of Examples 10-11 are shown in Table 6.

[0061] Table 6 - Experimental test results of Examples 10-11 Result analysis: The difference between Example 10-11 and Example 8 is that, when preparing high temperature resistant and fireproof cables, the composite flame retardant material prepared by Preparation Example 3 can better improve the comprehensive performance of high temperature resistant and fireproof cables.

[0062] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A high temperature resistant and fireproof cable, characterized in that: Including conductor, insulation layer, fireproof layer and outer sheath; The insulating layer is a quartz fiber wrapping layer coated with organic silicon-nano alumina sol insulating impregnation varnish; The fireproof layer comprises the following raw materials in parts by weight: 50-60 parts of polystyrene, 30-40 parts of low-density polyethylene, 14-20 parts of hydrotalcite, 7-10 parts of composite flame retardant material, 1.3-3.2 parts of compatibilizer, and 0.3-3 parts of crosslinking agent.

2. The high temperature resistant and fireproof cable according to claim 1, characterized in that: The preparation method of the composite flame retardant material comprises the following steps: A1. Adding hollow glass microspheres to a 2 wt% NaOH solution, mixing and stirring, filtering, washing, drying and then crushing to obtain pretreated hollow glass microsphere powder; A2, adding the pretreated hollow glass microsphere powder obtained in step A1 to ethanol and mixing, and then adding KH550 and mixing to obtain a mixed solution; A3, adding ammonium polyphosphate to ethanol and mixing and stirring to obtain an ammonium polyphosphate solution with a mass concentration of 18-22%; mixing the ammonium polyphosphate solution with the mixed solution obtained in step A2, filtering, washing, drying and then crushing to obtain ammonium polyphosphate-hollow glass microsphere powder; A4, adding sodium alginate to distilled water and mixing, then adding the ammonium polyphosphate-hollow glass microsphere powder obtained in step A3 and mixing, and freeze-drying to obtain the composite flame retardant material.

3. The high temperature resistant and fireproof cable according to claim 2, characterized in that: In the step A2, the weight volume ratio of the pretreated hollow glass microsphere powder, ethanol and KH550 is (5-7) g: 100 mL: (5-7) mL.

4. The high temperature resistant and fireproof cable according to claim 2, characterized in that: In step A3, the volume ratio of the ammonium polyphosphate solution to the mixed solution is (1-2):

1.

5. The high temperature resistant and fireproof cable according to claim 2, characterized in that: In the step A3, the weight ratio of the sodium alginate to the ammonium phosphate-hollow glass microsphere powder is 1:(1-3).

6. The high temperature resistant and fireproof cable according to claim 1, characterized in that: The weight ratio of the hydrotalcite to the composite flame retardant material is 1.8-2.4:

1.

7. The high temperature resistant and fireproof cable according to claim 1, characterized in that: The total weight of the hydrotalcite and the composite flame retardant material is 20.4-24.2% of the total weight of the raw materials of the fireproof layer.

8. The high temperature resistant and fireproof cable according to claim 1, characterized in that: The preparation method of the organic silicon-nano alumina sol insulating impregnating varnish is as follows: organic silicon resin and 30% nano alumina sol are stirred and mixed at a volume ratio of 1:2.5-3.5 for 2-3 hours to obtain the organic silicon-nano alumina sol insulating impregnating varnish.

9. The high temperature resistant and fireproof cable according to claim 1, characterized in that: The outer protective layer is polyurethane elastomer.

10. A method for preparing a high temperature resistant and fireproof cable according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, wrapping the conductor with quartz fiber, then coating the quartz fiber with organic silicon-nano alumina sol insulating impregnation varnish, and drying to obtain an insulating layer; S2, stirring and mixing the raw materials of the fireproof layer, and extruding and granulating; S3. The fireproof layer and the outer protective layer are sequentially coated on the outer surface of the insulation layer to obtain a high temperature resistant and fireproof cable.

Citation Information

Patent Citations

  • Preparation method of fireproof coating mica tape

    CN112992442A

  • Low-density solid flame-retardant buoyancy material as well as preparation method and application thereof

    CN116144220A

  • Fireproof cable and preparation method thereof

    CN117352219A